Research Methods for the Digital Humanities - levenberg, lewis; Neilson, Tai; Rheams, David (Springer, 2018)
This book introduces a range of digital research methods, locates each method within critical humanities approaches, presents examples from established and emerging practitioners, and provides guides for researchers. In each chapter, authors describe their pioneering work with an emphasis on the types of questions, methods, and projects open to digital humanists. Some methods, such as the translation of literary sources into digital games, are “native” to Digital Humanities and digital technologies. Others, such as digital ethnographies, are adopted and adapted from extensive traditions of humanities and social science research. All of the featured methods suggest future avenues for Digital Humanities research. They entail shifting ethical concerns related to online collaboration and participation, the storage and uses of data, and political and aesthetic interventions. They push against the boundaries of both technology and the academy. We hope the selection of projects in this volume will inspire new questions, and that their practical guidance will empower researchers to embark on their own projects. Amidst the rapid growth of Digital Humanities, we identified the need for a guide to introduce interdisciplinary scholars and students to the methods employed by digital humanists. Rather than delimiting Digital Humanities, we want to keep the field open to a variety of scholars and students. The book was conceived after a panel on digital research methods at a Cultural Studies Association conference, rather than a Digital Humanities meeting. The brief emerged out of contributions from the audience for our panel, conversation between the panel presenters, and the broader conference that featured numerous presentations addressing digital methods through a range of interdisciplinary lenses and commitments. The guide is designed to build researchers’ capacities for studying, interpreting, and presenting a range of cultural material and practices. It suggests practical and reflexive ways to understand software and digital devices. It explores ways to collaborate and contribute to scholarly communities and public discourse. The book is intended to further expand this field, rather than establish definitive boundaries.